Novel Method for Fire Retardancy of Cotton Fabrics Coated by Spinach Leaf Extract Assisted by Corona Discharge Plasma - Valentinus Galih Vidia Putra; Andrian Wijayono; Juliany Ningsih Mohamad (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2020)
The application of material physics in the functional textile field has been widely applied, one of which is plasma technology. In this research, the fire-retardant properties have been developed in the cotton fabric textile material using spinach leaf extract and comparison of fire-retardant resin on the market using plasma technology. The flame-retardant is applied to the cotton fabric using the atmospheric-pressure plasma method with a tip-cylinder electrode. The cotton fabric used is a cotton fabric that has undergone a process of bleaching and mercerization. In this research, two types of methods have been carried out, namely the immersion method on the fire-retardant resin substance with atmospheric pressure plasma pre-treatment and the immersion method on spinach leaf extract with atmospheric pressure plasma treatment. Research shows that there is an increase in the fire-retardant properties of cotton fabrics that have been given treatment. The assessment of fire-retardant properties was tested using the standard method of fire-retardant ASTM D6413-08 vertical method. In this research, atmospheric-pressure plasma treatment with a time variation of 2 minutes and 4 minutes has been carried out. The results showed that the cotton fabric treated with the immersion method on spinach leaf extract and atmospheric pressure plasma pre-treatment had better fire-retardant properties. It has also been found that the length of time the plasma treatment will affect the fire-retardant properties of cotton fabrics.